Half-metre sea-level fluctuations on centennial timescales from mid-Holocene corals of Southeast Asia - Aron J. Meltzner (Nature Portfolio, 2017)
Despite concern over anticipated eustatic sea-level rise, our understanding of past relative sea level, including regional deviations from the global average, is limited. Here, the authors show evidence for synchronous 0.6-m sea-level fluctuations between 6850 and 6500 yr BP at three sites across Southeast Asia.